Perancangan Sistem Informasi Manajemen Showroom Mobil Bekas di Putra Mobil Balikpapan dengan Metode Prototyping - Tezar Irawan; Aridhanyati Arifin (STIKes Ibnu Sina Ajibarang, 2024)
The used car showroom business conducts manual recording to document purchase transactions, sales transactions, vehicle unit financing, employee management, relying solely on the owner's memory. The risk lies in manual recording requiring significant time and attention, with possibilities of errors (duplication) in recording, loss, or damage. Hence, the utilization of information technology is necessary in managing the assets of the used car showroom and employee management, introducing a system called SIMOKAS (Sistem Informasi Manajemen Showroom Mobil Bekas). Steps in this research involve data collection, literature review, and system design. Data collection involves two approaches: interviews and observations. The applied system design method is Prototyping. System testing methods include Black Box Testing and Usability Testing. SIMOKAS testing occurred at Putra Mobil Balikpapan showroom, involving ten potential users. Based on functional testing through black box methods, SIMOKAS met requirements and functioned accordingly, managing vehicles, transactions, vehicle documents, and employees. Usability testing resulted in a total SUS score of 87.25, falling into the 'Acceptable' category for acceptability, receiving an 'A' grade on the grade scale, and being in the 'Best Imaginable' category in adjective rating. Thus, the conclusion drawn is that SIMOKAS is a system with good usability from the user's perspective.